Structural and functional status of myocardium and signal-averaged electrocardiogram data in essential arterial hypertension patients - V. I. Ruzov; R. Kh. Gimaev; V. A. Razin; O. V. Lukyanenko; A. N. Sapozhnikov; S. A. Sharangin (Кардиоваскулярная терапия и профилактика)
Aim. To study parameters of signal-averaged electrocardiography (SA-ECG) in patients with essential arterial hypertension (EAH), according to structural and functional cardiac disturbances. Material and methods. In total, 89 EAH patients were examined: 47 males and 39 females (mean age 51.5±7.2 years), including 24 patients with Stage I EAH, and 62 Р with Stage II EAH. Results. Late ventricular potentials (LVP) were registered in 29 EAH patients (33.7%). Patients with LVP had more advanced left ventricular and atrial dilatation (LV, LA). This resulted in increased LV end-systolic size, end-diastolic volume and size, LA size, compared to LVP-free participants. EAH patients with LVP had more progressed LV hypertrophy (LVH): increased thickness of interventricular septum, posterior wall, myocardial mass index. Assessing SA-ECG parameters in EAH patients with various LV remodeling types, the authors observed that LVP were more common for patients with eccentric LVH.